Corporate Brand Valuation-A Global Perspective - Yadagiri, M.; Sridhar, R. (Indian Journal of Marketing, 2009)
Financial evaluation and accounting procedures for brands have become subjects of intense debate. This is reflective of the importance of intangible assets in modern companies. The main purpose of valuing the brand is to determine the monetary benefit that accrues to the brand owner as a result of the brand. The valuation of brand is more concerned about its economic use. Economic valuation of brands are frequently done to serve the purposes such as setting royalty rates in licensing brands, evaluation of debt levels and risks, and estimating damages in trade marks disputes, etc. With the recent spate of mergers and takeovers there had been generated a pressing demand for review of accounting standards and regulations, so that not only acquired brands but also created brands are capitalized on the balance sheet.